Technology’s influence on Pentecostalism: Shaping perception and religious impact - Ndidzulafhi Mudau; Rendani Tshifhumulo (African Journal of Pentecostal Studies)
Background: The advancement of media and technology has significantly influenced religious expression, particularly among Pentecostals, facilitating novel engagement methods, outreach and worship.